Optimizing antithrombotic therapy following mitral valve repair: a comprehensive network meta-analysis - Mohamed Ibrahim Gbreel; Mohamed Hamouda Elkasaby; Marwa Hassan; Marc Ulrich Becher; Mahmoud Balata (BMC Cardiovascular Disorders)
Abstract Background Mitral regurgitation (MR) presents either as primary or secondary, with options for surgical or transcatheter repair. Thromboembolic risks following surgery are significant despite the use of antithrombotic medications, and guidelines for postoperative anticoagulation therapy lack consistency. This systematic review aims to compare antithrombotic medications after mitral valve repair (MVR). In this study, we intend to compare antithrombotic medications after MVR. Materials and methods The study followed the Cochrane handbook and PRISMA guidelines. We systematically searched databases (PubMed, Scopus, Ovid, Cochrane, Web of Science) until June 2024 for TMVR studies using specific criteria. Quality assessment utilized the Newcastle-Ottawa scale. Data extraction encompassed study characteristics and outcomes. Primary outcomes included thromboembolic events and bleeding within six months. Statistical analysis employed R software to assess heterogeneity and publication bias. Results From the 121 articles screened, 12 were included in the study. These cohort studies, involving 20,644 participants, spanned from 2008 to 2022. While most studies were of good to high quality, some exhibited lower quality. Analysis favored oral anticoagulants (OAC) over single antiplatelet therapy (SAPT) for reducing bleeding risk (RR = 0.31, 95% CI: [0.11–0.87], P < 0.05), with moderate heterogeneity. Thromboembolic events did not significantly differ among interventions. Transient ischemic attacks and stroke outcomes were similar between SAPT and vitamin K antagonists (VKA). Six-month mortality rates were comparable between SAPT and VKA, with notable heterogeneity and higher mortality with SAPT in one study. Qualitative synthesis highlighted procedural success rates and bleeding complications across different interventions in transcatheter mitral valve repair studies. Conclusion OACs showed a lower risk of bleeding compared to antiplatelet therapies, while VKAs and OAC + SAPT may reduce thromboembolic events. No significant differences were found in stroke, TIA, or short-term mortality. These findings support individualized therapy and highlight the need for further randomized trials.